Role of phosphatases in the biosynthesis of chlortetracycline in Streptomyces aureofaciens - Jechová, V; Curdová, E; Hostálek, Z (Folia microbiologica, 1982)
ATP diphosphohydrolase activity and inorganic pyrophosphatase reached two maxima during cultivation of the low- and high-producing variant of Streptomyces aureofaciens under conditions of phosphate limitation, i.e. after 30 and 70 h of cultivation. Increased levels of inorganic phosphate in a medium inhibitory to biosynthesis of chlortetracycline markedly decreased the levels of both enzymes. The ATP diphosphohydrolase activity was detected both in the supernatant and membrane fractions of the cell-free preparation of the mycelium.
Keywords: apyrasa; Apyrase; Culture Media; Phosphates; membrány; Chlortetracycline; fosfáty; Phosphoric Monoester Hydrolases; Pyrophosphatases; Streptomyces; fosfatasy; chlortetracyklin; Membranes; pyrofosfatasy; kultivační média